Structure modifications and mechanical properties of alloys exposed to pulsed ion beams; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 17, iss. 2 - Didenko A. N. Andrei Nikolaevich; Ligachev A. E.; Logachev E. I.; Pogrebnjak A. D.; Puchkareva L. N.; Nesterenko V. P.; Remnev G. E. Gennady Efimovich; Ruzimov Sh. M. (1986, 1986)
Title screen